2015
DOI: 10.1111/1742-6723.12394
|View full text |Cite
|
Sign up to set email alerts
|

INITIATE.D.: Impact of timing of INITIation of Antibiotic Therapy on mortality of patients presenting to an Emergency Department with sepsis

Abstract: Early administration of antibiotics specifically in patients with severe sepsis might be beneficial. Further studies within the ED are warranted to establish the effect of delayed antibiotics in a generalised sepsis cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
(44 reference statements)
1
22
0
Order By: Relevance
“…Additionally, it is possible that the critically ill may not have always been able to be reviewed prospectively because of difficulty in accessing medication charts during ‘rounds’, leading to a potential selection bias. Overall, times in this subgroup are consistent with those recently published in other Australian EDs …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, it is possible that the critically ill may not have always been able to be reviewed prospectively because of difficulty in accessing medication charts during ‘rounds’, leading to a potential selection bias. Overall, times in this subgroup are consistent with those recently published in other Australian EDs …”
Section: Discussionsupporting
confidence: 90%
“…Overall, times in this subgroup are consistent with those recently published in other Australian EDs. 22 A significant improvement was observed in the proportion of patients administered antibiotics within 30 min of presentation to about 50% of cases but presents an area of further improvement. Similarly, the proportion of patients prescribed antibiotics within 60min of presentation showed no significant change and may be further improved through focused quality improvement initiatives.…”
Section: Discussionmentioning
confidence: 91%
“…14 Thirteen studies were from the USA, 12,15-26 eight from Spain, 27-34 five from Italy, 35-39 four from Korea, 40-43 three each from Turkey 44-46 and Israel, 47-49 two each from the Netherlands 50,51 and the UK, 52,53 and single studies from Denmark, 54 Germany, 55 Norway, 56 and Australia. 57 Of the 46 studies 34 were retrospective in design and only three of these studies were case controlled. 16,36,49 Whilst a few studies focused on specific patient groups, most included all adult patients.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of delayed therapy on BSI-associated mortality combined with the analysis of GP and GN organisms were reported in five of the 12 studies and reported a two-fold increase. 15,50,52,56,57 Only two of the twelve studies were case controlled and reported on the impact of Methicillin Resistant Staphylococcus aureus (MRSA) with a delay in therapy of two days, resulting in an odds of mortality of 1.85 (95%CI: 0.094-3.64, P=0.074) 16 and patients with BSI due to ESBL organisms with a delay in therapy of 48 hours resulting in an OR of 25.1 (95%CI: 10.5-60.2, P≤0.001). 49 Overall a greater impact was seen in GN resistant infections ranging from 3 to 25-fold increases in the risk of BSI-associated mortality.…”
Section: Impact Of Delayed Therapymentioning
confidence: 99%
“…Repeatedly over the past few years, investigators have reported that more rapid administration of antibiotics and completion of sepsis bundles leads to lower sepsis mortality. 2,4,5 The implication is that clinicians should initiate sepsis protocols expeditiously to improve survival. However, the vast majority of these studies cast these conclusions without considering and mentioning the outcomes of nonseptic patients with systemic inflammatory response syndrome due to noninfectious causes (eg, pancreatitis, viral infections, cardiogenic shock, hypovolemic shock, and adrenal insufficiency) who received prompt but unnecessary antimicrobial therapy, 2,4,5 Quite possibly, a significant fraction of these nonseptic patients who receive unnecessary antibiotics and sepsis protocols could have poorer outcomes.…”
mentioning
confidence: 99%